Combination of Tevatron Searches for the Standard Model Higgs Boson in the W+W- Decay Mode - Aaltonen, T.; Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Adelman, J.; Aguilo, E.; Alexeev, G. D.; Alkhazov, G.; Bose, T.; et al. (Amer Physical Soc, 2010)
We combine searches by the CDF and D0 Collaborations for a Higgs boson decaying to W+W-. The data correspond to an integrated total luminosity of 4.8 (CDF) and 5.4 (D0) fb(-1) of p (p) over bar collisions at root s = 1.96 TeV at the Fermilab Tevatron collider. No excess is observed above background expectation, and resulting limits on Higgs boson production exclude a standard model Higgs boson in the mass range 162-166 GeV at the 95% C.L.